(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article reflects the use of plant names and their genealogical origin in the ghazal verses of the genius poet in the collection "Khazoin ul-maoniy", the semantic meaning of the names of plants and fruit trees, flowers and vegetables used in the name of the plant. In addition, the assimilation of plant names, the frequency of their use in ghazal verses are also given.